PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, KEPERCAYAAN, DAN NILAI NASABAH TERHADAP KEPUASAN NASABAH (Studi pada PD BPR BKK Purbalingga Cabang Bukateja) - Okky Mudinarko; Suyoto Suyoto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
This study aimed to determine to correlation between four independent variables of quality servive, quality products, trust, and customer value on customer satisfaction variable. This study was explanatory research using quantitative approach of multiple regression. Sample of this study were 103 customers of the bank. Data analysis techniques used in the study were multiple regression analysis, t-test, F-test, and classical assumption testing. Data of this study was taken using quistionnaire distributed to customers of the bank and analyzed using SPSS 16 version.The resulf of F-test analysis showed that factor of service quality, product quality, trust and customers value gave effect simultaneously with 52,7% of the value of Adjusted R Square on customer satisfaction in the bank. In addition, 47,3% of the remaining value were affectted by other factors which were not discussed in this study. The result of partial t-test showed that service quality gave the biggest effect on customer satisfaction in the bank. The more accessable the bank service was, the more interested people in the bank would be. Marketing strategy showed significant effect in improving service quality. Thus, the better the marketing management in the bank was, the more interested people in the bank would be.